The Influence of Leadership Dynamics and Workplace Stress on Employee Performance in the Entrepreneurial Sector and the Moderating Role of Organizational Support - Ahli, Reem; Hilmi, Mohd Faiz; Abudaqa, Anas (Pandawan, 2024)
Employee performance is crucial to the success of organizations, particularly in the entrepreneurial sector. Various factors, such as abusive supervision, job stress, turnover intention, and agile leadership, play a significant role in determining performance outcomes. This study aims to evaluate how perceived organizational support moderates the effects of these factors on employee performance in public firms in the UAE. Data were gathered from a valid sample of 211 respondents. The analysis employed measurement and structural model assessments using Smart PLS version 4.0. The results validated the internal consistency reliability, convergent validity, and discriminant validity of the latent constructs. Structural equation modeling indicated significant effects of agile leadership, abusive supervision, and job stress on employee performance. Furthermore, perceived organizational support was found to significantly moderate the relationships between agile leadership and employee performance, abusive supervision and employee performance, and job stress and employee performance. Based on these findings, several policy recommendations were made for public sector firms in the UAE, particularly highlighting the importance of supportive leadership practices in enhancing employee performance within the entrepreneurial sector.